Physical, behavioural, and psychosocial factors associated with childhood and adolescent obesity: a study from the United Arab Emirates - Ashraf, Tanveer; Pearce, Alaina L.; Helal, Radwa; Saidi, Sarah; Vaidya, Chandan J.; Lessan, Nader (Frontiers in Pediatrics, 2025)
AimsPaediatric obesity is associated with both physical and psychosocial health. Whether those associations, which are most widely reported in Western samples, are also observed in other sociocultural settings is not well known. This study aimed to characterise lifestyle, physical, and psychological characteristics associated with excess weight in Emirati youth, a population that has not been widely studied.Materials and methodsHeight and weight were measured for 107 youth (46 male; 7–17 years) from Abu Dhabi. A detailed medical history was obtained from the Imperial College London Diabetes Centre. Parents reported relevant family history and demographics, sleep using the Children's Sleep Habits Questionnaire, and mental health problems using the Strengths and Difficulties Questionnaire.ResultsOlder youth and those with a family history were more likely to have obesity; however, weight status did not differ by sex, income, or parental education. Anaemia was more prevalent in youth with a healthy weight, while hyperlipidemia was more prevalent in youth with overweight or obesity. Obesity was associated with disordered breathing during sleep but not with sleep times or duration. Overall, weight status did not relate to mental health problems; however, obesity was associated with a greater risk for peer problems in females but not males.ConclusionsThese results highlight factors that may play a role in culturally specific drivers of paediatric obesity in the Middle East and will help to natively tailor prevention and intervention efforts.